Better Understanding the Orthopaedic Burden of Neurosurgical Intervention for Drug-Resistant Epilepsy in Paediatric Patients - Lin, Adrian J; Talathi, Nakul S; Gajewski, Nicholas; Thompson, Rachel M (Pediatric neurosurgery, 2025)
Hemispherectomies, hemispherotomies, and lobectomies of the brain are neurosurgical techniques used to treat drug-resistant epilepsy (DRE). While effective for seizure control, these neurosurgical interventions can produce significant functional deficits including hemiparesis and iatrogenic cerebral palsy. In this study, we aimed to evaluate the resulting MSK pathology following surgery for DRE so that we may establish the incidence of new MSK pathology, identify risk factors for developing MSK pathology, and guide orthopaedic follow-up care. A retrospective chart review of 168 paediatric patients who underwent a brain hemispherectomy, hemispherotomy, or lobectomy between 2009 and 2018 was performed. Data including pre-existing neurological and orthopaedic conditions, presence of MSK pathology that emerged post-neurosurgical procedure, documented referral to orthopaedics, and post-operative interventions were collected. A multivariate logistic regression model was used to correlate predictive variables with the risk for developing new MSK pathology. Of the 168 patients included, 45.2% (n = 76) developed a new MSK condition post-operatively. Of those with new MSK pathology, 30.3% (23) received orthopaedic follow-up. Of those, 34.8% (8) underwent a subsequent orthopaedic surgery. The median time to diagnosis of emerging MSK pathology following neurosurgical intervention was 0.7 months (range: 0-128 months), while the median time from emergence of symptoms to orthopaedic follow-up was 9.5 months (range: 2-161 months). Of the 28 patients who had MSK pathology prior to neurosurgical intervention, 42.8% (n = 12) were seen by orthopaedic providers following neurosurgery, of which 58.3% (n = 7) required orthopaedic surgery. Older age at the time of initial neurological surgery was significantly associated with decreased risk for developing new post-operative MSK pathology (OR 0.985, 95% CI: 0.979-0.911, p < 0.001), while repeat or revision neurosurgery was associated with increased risk (OR 3.728, 95% CI: 1.530-9.083, p < 0.01). Paediatric patients who undergo hemispherectomies, hemispherotomies, or lobectomies for DRE are subject to a significant post-operative burden of MSK disease, yet less than 1/3 of newly-affected patients receive orthopaedic follow-up - highlighting a gap between the need for and provision of orthopaedic care in this population.